Impact of E-Commerce Applications on Non- Financial Peformance of Selected Online Retail Enterprises in Lagos State, Nigeria - ONIKOYI, Idris Adegboyega; BABATUNDE, Bayode Olusanya; ODEH, Callistus Destiny (The Journal of Accounting and Management, 2022)
This study examined the impact of e- commerce applications on non-financial performance of selected online retail enterprises in Lagos State, Nigeria with emphasis on Jumia and Konga e- retail outlets. Three specific objectives were formulated for the study and they are; to investigate the effect of electronic advertising on customers’ patronage in the selected online retail enterprise; to examine the influence of electronic customer service support system on customers’ satisfaction in the selected online retail enterprise; and to evaluate the effect of e- order and delivery on customers’ satisfaction in the selected online retail stores; The sample size was 384. Data was sourced through the use of a structured questionnaire and the study adopted purposive and stratified sampling technique. Descriptive statistics and regression analysis were both adopted as methods of data analysis. Results from the test of first hypothesis showed that electronic advertising had significant positive effect on customers’ patronage with R2 value = (0.619) and F (4, 379) = 153.969, p < 0.05. Also, the result of hypothesis two revealed that showed that customer service support system significantly had a positive effect on the level of customer’s satisfaction with F (5, 378) = 9.214, p < 0.05. Furthermore, hypothesis three results revealed that e-order and delivery variables had significant and positive impact on customer’s satisfaction with F (4, 379) = 105.212, p < 0.05. This study thus rejected all null hypotheses and accepted the alternative hypothesis and concludes that e-commerce applications variables had a positive impact on non- financial performance of the selected e- retail outlets. The study recommends that there is need for e- retail enterprises to maintain consistency in the quality of products/ services ordered online by customers and what is delivered to them and priority should be given to customers’ complaints through e-customers’ service support system. Complaints most times are form of feedback and ability to provide solutions to these complaints puts the e- retail outlets in a much better way to serve the customers while providing utmost satisfaction